Educação e Ideologia: uma análise crítica dos fundamentos teóricos e metodológicos da extensão rural no Brasil (1953-1974) - Wolfart, Cíntia (2023)
The theme of this thesis is the history of the Rural Extension agency in Brazil. The aim is to analyze the theoretical and methodological foundations that guided the training activities of rural extension workers between 1953 and 1974. In 1953, extension was organized and supervised by the Agricultural Technical Offices (ETA) and by the Credit Associations and Rural Assistance (ACAR's), and in 1974, it was the milestone of creation of the Brazilian Company of Technical Assistance and Rural Extension (EMBRATER), which was responsible for absorbing the entire structure of the Brazilian Association of Credit and Rural Assistance (ABCAR) from 1956 Presenting a philanthropic rhetoric, the Rural Extension sought to disseminate agricultural teachings called “useful” and practical to the population, with a view to boosting production and “improving the quality of life in the countryside”. Through the premise of forming an ideal type of rural producer, suited to the precepts of modernization, for that, it was necessary to overcome the barrier that Brazilian agriculture imposed for modernization and industrial advancement. Several institutions, such as: Alliance for Progress, American International Association, USAID, Rockefeller Foundation, World Bank, Ford Foundation, among other civil society associations, made use of a bourgeois modernizing project with conservative characteristics, which had a pedagogical practice that involved several areas of knowledge: psychology, sociology, philosophy, administration and economics. This knowledge was mobilized with a view to training rural extensionists, organic intellectuals of capital, for the purpose of spreading capitalism in the countryside. Innovative diffusionism, originating from the standards and values of imperialist nations, was another work methodology developed by Rural Extension in the period studied and which resulted in transformations in the way of life in rural areas and which were defining for the permanence or exclusion of workers in the field. The central hypothesis of this thesis is that Rural Extension in Brazil has appropriated several theoretical conceptions and methodological tools in the extension training process to guarantee the consolidation of capitalism in the countryside. The race for the “training” of organic intellectuals, via Extensionist Training Centers, in the context of the Cold War, had as its objective the production of active consensus on the periphery and voluntary submission to the project of conservative modernization. To ensure increased production efficiency in the field, Rural Extension appropriated technical and business training methodologies, supported by Allen's Four Steps and the TWI system. One of the main objectives was to form a leadership, supervision and instruction board, capable of training and influencing rural producers in an environment of tranquility and security for the adaptation of the workforce to the demands of capital.